Molecular Studies and an ex vivo Complement Assay on Endothelium Highlight the Genetic Complexity of Atypical Hemolytic Uremic Syndrome: The Case of a Pedigree With a Null CD46 Variant - Piras, Rossella; Iatropoulos, Paraskevas; Bresin, Elena; Todeschini, Marta; Gastoldi, Sara; Valoti, Elisabetta; Alberti, Marta; Mele, Caterina; Galbusera, Miriam; Cuccarolo, Paola; Benigni, Ariela; Remuzzi, Giuseppe; et al. (Frontiers in Medicine, 2020)
Atypical HUS (aHUS) is an ultra-rare disease characterized by microangiopathic hemolysis, thrombocytopenia and renal impairment and is associated with dysregulation of the alternative complement pathway on the microvascular endothelium. Outcomes have improved greatly with pharmacologic complement C5 blockade. Abnormalities in complement genes (CFH, CD46, CFI, CFB, C3 and THBD), CFH-CFHR genomic rearrangements and anti-FH antibodies have been reported in 40-60% of cases. The penetrance of aHUS is incomplete in carriers of complement gene abnormalities, and multiple hits, including the CFH-H3 and CD46GGAAC risk haplotypes and the CFHR1*B risk allele, as well as environmental factors, contribute to disease development. Here we investigated the determinants of penetrance of aHUS associated with CD46 genetic abnormalities. We studied 485 aHUS patients and found CD46 rare variants (RVs) in about 10%. The c.286+2T>G RV was the most prevalent (13/485) and was associated with less than 30% penetrance. We conducted an in-depth study of a large pedigree including a proband who is heterozygous for the c.286+2T>G RV, who experienced a severe form of aHUS and developed end-stage renal failure. The father and paternal uncle with the same variant in homozygosity, and six heterozygous relatives, are unaffected. Flow cytometry analysis showed about 50% reduction of CD46 expression on blood mononuclear cells from the heterozygous proband and over 90% reduction in cells from the proband’s unaffected homozygous father and aunt. Further genetic studies did not reveal RVs in known aHUS-associated genes or common genetic modifiers that segregated with the disease. Importantly, a specific ex-vivo test showed excessive complement deposition on endothelial cells exposed to sera from the proband, but also from his mother and maternal uncle, who do not carry the c.286+2T>G rare variant, indicating that they share a circulating defect that results in complement dysregulation on the endothelium. These results highlight the complexity of the genetics of aHUS and indicate that CD46 deficiency may not be enough to induce aHUS. We hypothesize that the proband inherited from his mother a genetic abnormality in a complement circulating factor that has not been identified yet, which synergized with the CD46 rare variant in predisposing him to the aHUS phenotype.